Etiology of Bacteremia in Young Infants in Six Countries. Issue 1 (January 2015) - Hamer, Davidson H.; Darmstadt, Gary L.; Carlin, John B.; Zaidi, Anita K. M.; Yeboah-Antwi, Kojo; Saha, Samir K.; Ray, Pallab; Narang, Anil; Mazzi, Eduardo; Kumar, Praveen; Kapil, Arti; Jeena, Prakash M.; et al.
Abstract : Background: Neonatal illness is a leading cause of death worldwide; sepsis is one of the main contributors. The etiologies of community-acquired neonatal bacteremia in developing countries have not been well characterized. Methods: Infants <2 months of age brought with illness to selected health facilities in Bangladesh, Bolivia, Ghana, India, Pakistan and South Africa were evaluated, and blood cultures taken if they were considered ill enough to be admitted to hospital. Organisms were isolated using standard culture techniques. Results: Eight thousand eight hundred and eighty-nine infants were recruited, including 3177 0–6 days of age and 5712 7–59 days of age; 10.7% (947/8889) had a blood culture performed. Of those requiring hospital management, 782 (54%) had blood cultures performed. Probable or definite pathogens were identified in 10.6% including 10.4% of newborns 0–6 days of age (44/424) and 10.9% of infants 7–59 days of age (39/358). Staphylococcus aureus was the most commonly isolated species (36/83, 43.4%) followed by various species of Gram-negative bacilli (39/83, 46.9%; Acinetobacter spp., Escherichia coli and Klebsiella spp. were the most common organisms). Resistance to second and third generation cephalosporins was present in more than half of isolates and 44% of the Gram-negative isolates were gentamicin-resistant. Mortality rates were similar in hospitalized infants with positive (5/71, 7.0%) and negative blood cultures (42/557, 7.5%). Conclusions: This large study of young infants aged 0–59 days demonstrated a broad array of Gram-positive and Gram-negative pathogens responsible for community-acquired bacteremia and substantial levels of antimicrobial resistance. The role of S. aureus as a pathogen is unclear and merits further investigation.